Aspirin-Induced Mortality in AedesaegyptiMosquitoes - Fischer, Reagan; Haeker, Cody; Silver, Kristopher (My University, 2018)
The Aedes aegypti mosquito is a vector for many dangerous diseases including yellow fever, Zika, Chikungunya, and Dengue virusest Currently, the best method for suppressing infection with these viruses is by controlling their arthropod vectors, however the continual use of conventional insecticides to control Ae. aegypti mosquitoes has led to the development of significant levels of resistance to these chemicals. Accordingly, new methods are needed. Anecdotal evidence has suggested that mosquitoes may be sensitive to treatment with aspirin or its metabolites in a blood meal. Previous studies with aspirin in insects have mainly focused on the ability of aspirin to enhance longevity and lifespan in Drosophila melanogaster and crickets, but one study showed that aspirin in water where larvae are developing causes significant mortality and signs of neurotoxicity. While treating larvae in this manner is not practical for vector control, this result, in addition to the anecdotal evidence, prompted the question of whether aspirin consumed in a blood meal can cause mortality in adult mosquitoes. Accordingly, we fed adult female Ae. aegypti mosquitoes differing concentrations of aspirin in human blood and measured mortality for four days following the blood meal. The concentrations chosen correspond to plasma concentrations of aspirin in humans who have consumed 100 mg (a baby aspirin), 1 g (normal adult dose), or 10 g (overdose), respectively. Our results indicate that these concentrations of aspirin are insufficient to cause significant mortality in the mosquitos. Although unsuccessful, modification of our methods, use of a different mosquito species, or use of aspirin metabolites in our bioassays may yet show a significant impact of aspirin consumption on mosquito survival.
Keywords: Fall 2018